Synthesis and characterization of conductive polyaniline nanocomposite containing fluorene. (December 2017) - Song, Hui; Zhang, Chengxiang; Li, Tingxi; He, Xiaolong; Han, Yongqin; Wang, Yanmin; Wang, Qing
Fluorene, an excellent electroluminescent material, has been used as a core to synthesize a core–shell fluorene/polyaniline (fluorene/PANI) composite using ammonium persulfate as an oxidant. The influence of the fluorene–aniline molar ratio and the oxidant–aniline molar ratio on the resistance of the composite was investigated, and the crystallinity, structure, and morphology of the fluorene/PANI composite were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy. The results indicate that the fluorene/PANI composite has a core–shell structure and exhibits good conductivity. A more planar conformation of PANI could be formed because of strong π–π interactions between the fluorene core and the PANI shell.